HUBUNGAN POLA MAKAN DENGAN STATUS GIZI ANAK PRA SEKOLAH DI PAUD TUNAS MULIA CLAKET KECAMATAN PACET MOJOKERTO: RELATIONSHIP BETWEEN DIET WITH NUTRITIONAL STATUS OF PRE-SCHOOL CHILDREN IN PAUD TUNAS MULIA CLAKET, PACET MOJOKERTO DISTRICT - Sa'diya, Lida Khalimatus (Jurnal Kebidanan Midwiferia, 2015)
Nutrients have strong relationship with health and intelligence as well as development of the children. If the dietary habit is not reached perfectly, it can disturb the future growth. This study was aimed to determine the relationship between dietary habits to the nutritional status of pre-school children in PAUD Tunas Mulya Claket Village Pacet Mojokerto.This study was used correlation analytic design with cross sectional approach. The populations were all mothers and preschool children in PAUD Tunas MulyaClaket Village Pacet Mojokerto as amount 17 children. The sampling technique was used total sampling. The results of this study were suggested that most of preschoolers had good dietary habits those were11 children (64.7% of respondents), and almost all preschool children had normal nutritional status those were13 children (76.4% of respondents).From 6 respondentswho had not good dietary habits, no one (0%) had overweight nutritional status, and9 respondents (81.8%) had good dietaryhabits, they had normal nutritional status.The data analysis was used Spearman's rho test with ρ value (0.038) <α (0.05) so that H0 rejected and H1 accepted means that there was relationship between dietary habits and nutritional status of preschool children in PAUD Tunas Mulya Claket Village Pacet Mojokerto. Nutritional status was determined by the adequacy of the food and the ability of the body that contain the nutrients necessary for health so that needed good diet to get the normal nutritional status. Health workers must monitor children's nutrition through IHC.